Slobodan Milošević: a case-study of the criminal leader - Clark, Janine N. (2006)
This thesis is a case-study of Slobodan Milosevic as a prototype of the "criminal" leader. Challenging the existing consensus among Western liberals, for whom Milosevic is unquestionably criminal, it asks whether and to what extent Milosevic is a criminal leader. It approaches this by first dissecting the Western construction of Milosevic as a criminal leader into its key components -- his actions and intentions, his motivations, his personality and psychology, and his comparison with other "criminal" leaders. This normative-driven construction is then empirically tested, using two main sources. The speeches of Milosevic, fundamentally misrepresented by many Western commentators, are analyzed. The second primary source used is semi-structured interviews (supported by public opinion poll data). Strongly influenced by bottom-up studies of the Hitler and Stalin regimes, two leaders that can be seen as crucial cases of the criminal leader, this research is particularly concerned with exploring how ordinary people in Serbia - heavily neglected in the existing Western literature - view Milosevic. This allows us to ascertain whether and to what extent the Western, liberal construction of Milosevic as a criminal leader has domestic/field validity. What the interview data reveals is a sharp discrepancy between the external (Western) and domestic (Serbian) viewpoints. The Serbian interviewees overwhelmingly view Milosevic not as a criminal leader, but as a "bad" (unsuccessful) leader and/or as a victim. This discrepancy is translated into, and used to develop, a general concept of the criminal leader. This conceptualization emphasizes both the externally constructed nature of the criminal leader (policy dimension) and the importance of studying the criminal leader from below (domestic dimension).